MODEL OF THEMATIC INTERPRETOTION OF THE VIEW IMAGES - Butko, Ihor (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2021)
The subject matter of the article is thematic interpretation of species images. The goal of the work is to develop a model for thematic interpretation of species images, which will be based on the model for the formation of species images and additionally take into account geographic zoning. The following task was solved in the article: development of a model of thematic interpretation of view images, which takes into account the shortcomings of existing models and is based on the model of formation of view images, carries out the reverse transformation of the image coordinates into geospatial coordinates and clustering the image into separate classes according to their color and texture, additionally taking into account geographic zoning, which provides the possibility of advanced analysis and forecasting the temporal dynamics of data in geospatial information processing systems. The following methods used are – mathematical apparatus of the theory of matrices, methods of mathematical modelling, methods of data clustering, methods of differential calculus, methods of digital image processing. The following results were obtained – groups of existing models for interpreting the results of remote sensing of the Earth, their advantages and disadvantages have been analyzed; a mathematical model of the formation of a species image for a section of the earth’s surface has been formulated in general form; a mathematical model of thematic interpretation of species images was formulated in general form; the operator of transformation of coordinates, operators of clustering, operators of zoning and their explicit form are considered; a model of thematic interpretation of species images in operator form is obtained. Conclusions: for the first time, a model of thematic interpretation of view images was developed, which, based on the model of formation of view images, carries out the inverse transformation of coordinates into geospatial coordinates and clustering by their color and texture, additionally taking into account geographical zoning, which provides the possibility of advanced analysis and forecasting of the temporal dynamics of data in processing systems geospatial information.